CURRENT STATE AND TRENDS OF ENVIRONMENTALLY SAFE ENGINESDEVELOPMENT - Тихонов, Є. О.; Логінов, Г. С. (Science-based technologies, 2009)
Existing basic approaches to creation of ecologically careless engines for the mobile transport which has been not adhered directly to local energy sources are considered: electric motors on chemical battery, hydrogen engines, hybrid motors, engine on compressed air, Stirling engine and biofue applicationl.